Factors influencing own source revenue collection in local government authorities in Tanzania: A case study of Mpwapwa and Kongwa District Councils - Malangalila, Joseph Gaudence (Mzumbe University, 2024)
A dissertation submitted in partial/fulfillment of the requirements for the award of the Degree of Master of Science in Accounting and Finance (MSc. A&F) of Mzumbe University